NATO defense spending in 2023: Implications one year after Russia's invasion of Ukraine - Florian Dorn; Niklas Potrafke; Marcel Schlepper (CESifo GmbH, 2023)
War is raging close to NATO's Eastern border. Russia has attacked Ukraine and threatens those states that in the past had been part of Moscow's sphere of influence. Many of them are now member states of NATO. As a collective defense alliance, this poses a threat to all NATO members. Since the ability to defend against an aggressor does not come for free, defense spending will be on the agenda at the NATO Summit in Vilnius in July 2023. NATO Secretary General Jens Stoltenberg has already expressed his expectation that all member states no longer see the 2% target as a mere ambition, but as the floor for their future defense spending. This paper presents first results for the expected defense spending of the 30 NATO members and the candidate country Sweden in 2023.
Keywords: 330; Militärausgaben; NATO-Staaten; Krieg; Ukraine; Russland